Tendenser i idrætshistorisk forskning 1995-2005 - Madsen, Bo Vestergård; Nielsen, Niels Kayser (Forum for Idræt, 2004)
Tendencies in research into sporting history 1995-2005 This historiographic article sets out some of the main features of Danish research into sporting history over the past 10 years. After a discussion of the various forums and avenues that have been available to such research, the article centres on the following research themes: sporting organisations and institutions, local history and sport, sport and politics – including gender aspects – and the body, public information and democracy.